Pengaruh Lingkungan Kerja dan Kompensasi terhadap Kinerja Guru Dengan Motivasi Sebagai Variabel Intervening di SMAN 1 Tiumang - Deris Herdiansyah; Desi Permata Sari; Della Asmaria Putri (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to explore and evaluate the impact of the work environment and compensation on teacher performance at SMAN 1 Tiumang, with motivation considered as an intervening variable. The analysis was conducted using Structural Equation Modeling (SEM) with the SmartPLS 3.0 application. The research sample consisted of all teachers working at SMAN 1 Tiumang. The findings indicate that the work environment has a significant positive effect on teacher motivation. Similarly, compensation also plays a crucial role in enhancing motivation, demonstrating a significant and positive influence. However, while the work environment has a positive yet relatively small effect on teacher performance, compensation contributes positively and significantly to improving teacher performance. Motivation is also found to have a significant positive impact on teacher performance. Nevertheless, the study reveals that motivation does not mediate the relationship between the work environment and teacher performance, nor does it mediate the link between compensation and teacher performance.